The Factors Related To The Performance Of Health Workers In Finding New Cases Of TB Through Contact Investigation At Hutabaginda Community Health Center, North Tapanuli Regency - Nababan, Saroha Ingot Hatoguan; Gurusinga, Rahmad (JURNAL KESMAS DAN GIZI (JKG), 2024)
Background: Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis. Until now, tuberculosis is still a world health problem. It is estimated that about one third of the world's population has been infected by the bacteria. Every second there is one person infected and in the next decade no less than 300 million people will be infected by pulmonary tuberculosis. Objectives: to analyze factors related to the performance of health workers in finding new TB cases through contact investigations at the Hutabaginda Community Health Center, North Tapanuli Regency. Research method: This type of research is quantitative research in the nature of an analytical survey with a cross sectional design. The population in this study were all health workers involved in finding new TB cases through contact investigations at the Hutabaginda Community Health Center, North Tapanuli Regency, totaling 63 people. Results: The results of this research are that there is a relationship between the factors ability, clarity, help, incentive, evaluation, validity and environment with the performance of health workers in finding new TB cases through contact investigations at the Hutabaginda Community Health Center, North Tapanuli Regency Conclusion: With the performance of health workers in the discovery of new TB cases through contact investigation at the Hutabaginda Health Center, North Tapanuli Regency.